Deciphering the properties of hemp seed oil bodies for food applications: Lipid composition, microstructure, surface properties and physical stability. (December 2021) - Lopez, Christelle; Novales, Bruno; Rabesona, Hanitra; Weber, Magalie; Chardot, Thierry; Anton, Marc
Graphical abstract: Highlights: Oil bodies are natural lipid droplets abundant in hemp seeds. Aqueous extraction by grinding permits the recover of hemp seed oil bodies and protein bodies. Hemp seed oil bodies contain well-balanced PUFA, lutein, γ-tocopherol and phytosterols. Oil bodies hemi-membrane is a sophisticated mixture of proteins and phospholipids. The physical stability of oil bodies is altered by pH, NaCl and CaCl2. Abstract: Hemp seed oil bodies (HSOBs) are of growing interest in response to the demand of consumers for healthy and natural plant-based food formulations. In this study, we used minimal processing including aqueous extraction by grinding and centrifugation to obtain HSOBs. We determined the lipid composition of HSBOs, their microstructure, and the impact of the homogenization pressure, pH and minerals on their surface properties and the physical stability of the emulsions. HSOBs contain high levels of well-balanced PUFA with LA/ALA = 2.9, γ-tocopherol, lutein and phytosterols. The mean diameter of HSOBs was 2.3 ± 0.1 μm with an isoelectric point in the range of pH 4.4 to 4.6. Homogenization of hemp seed extracts induced a decrease in the size of HSOBs but did not eliminate the sedimentation of the protein bodies composed of the globulin edestin. By changing the surface properties of HSOBs, pH values below 6 and NaCl induced the aggregation of HSOBs, while CaCl2 induced both aggregation and membrane-fusion mediated coalescence of HSOBs by involving probably the anionic phospholipids together with membrane proteins. This study will contribute to extend the range of novel food products and designed emulsions containing hemp seed proteins and oil bodies.